Adventitial Progenitor Cells of Human Great Saphenous Vein Enhance the Resolution of Venous Thrombosis via Neovascularization - Siying Ling; Zhen Ma; Yong Teng; Xuemei Jiang; Junning Cheng; Ruihao Li; Mingyi Zhang; Hailong Luo; Yikuan Chen (Stem Cells International)
Background. Vascular adventitia contains progenitor cells and is shown to participate in vascular remolding. Progenitor cells are recruited into the venous thrombi in mice to promote neovascularization. We hypothesized that the adventitial progenitor cells of human great saphenous vein (HGSV-AdPC) enhance the resolution of venous thrombosis via neovascularization. Methods. Human great saphenous vein (HGSV) was harvested from the patients with great saphenous vein varicose and sectioned for immunohistochemistry, or minced for progenitor cell primary culture, or placed in sodium dodecyl sulfate solution for decellularization. Human venous thrombi were collected from patients with great saphenous vein varicose and superficial thrombophlebitis. Infrarenal abdominal aorta of New Zealand white rabbits was replaced with interposing decellularized vessel, and the patency of the grafts was confirmed by ultrasonic examination. Animal venous thrombi in the left infrarenal vena cava of mice were produced with Prolene suture ligation and ophthalmic force clipping of this portion. After HGSVs were digested by collagenase, the CD34+CD117+ HGSV-AdPC were isolated on FACS system, labelled with CM-Dil, and transplanted into the adventitia of infrarenal vena cava of nude mice. The percentage of thrombus organization area to the thrombus area was calculated as the organization rate. The thrombus cell, endothelial cells, and macrophages in the thrombi were counted in sections. Cell smears and frozen sections of human saphenous veins and venous thrombi were labeled with Sca1, CD34, CD117, Flk1, CD31, and F4/80 antibodies. The CD34+CD117+ HGSV-AdPC were cultured in endothelial growth medium with vascular endothelial growth factor (VEGF) to induce endothelial cell differentiation and analyzed with real time-PCR, Western blotting, and tube formation assays. Results. Immunohistochemical staining showed that the CD34+CD117+ cells were located within the adventitia of HGSVs, and many CD34+ and CD117+ cells have emerged in the human venous thrombi. The number of progenitor cells within the marginal area of 7 days mice thrombi was shown to be Sca1+ ≈21%, CD34+ ≈12%, CD117+ ≈9%, and Flk1+ ≈5%. Many CD34+adventitial progenitor cells have migrated into the decellularized vessels. FACS showed that the number of CD34+CD117+ HGSV-AdPC in primary cultured cells as 1.2±0.07%. After CD34+CD117+HGSV-AdPC were transplanted into the adventitia of nude mice vena cava with venous thrombi, the organization rate, nucleate cell count, endothelial cells, and macrophage cells of thrombi were shown to be significantly increased. The transplanted CD34+CD117+ HGSV-AdPC at the adventitia have crossed the vein wall, entered the venous thrombi, and differentiated into endothelial cells. The CD34+CD117+ HGSV-AdPC in the culture medium in the presence of VEGF-promoted gene and protein expression of endothelial cell markers in vitro and induced tube formation. Conclusions. HGSV-AdPC could cross the vein wall and migrate from the adventitia into the venous thrombi. Increased HGSV-AdPC in the adventitia has enhanced the resolution of venous thrombi via differentiating into endothelial cells of neovascularization.